Project scenarios for the regeneration of sacred spaces (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
Sacred space is a unique type of architectural environment with historical(temporal), social, cultural, semantic, ritual-functional, spatial-architectural, psycho-emotional(perceptual), memorial, landscape, and ethical aspects that organize a visible and invisiblemultilayered system. In the course of historical development, such spaces built the spatial structureof the city and functioned as a center of socio-spatial interactions, collective memory, and identity.Sacred territories have undergone a complex evolutionary path. Cultural, political, and socialchanges have led to transformations and changes in functional purpose, as well as significantdestruction. Each historical stage has led to changes or the loss of sacred function, creating newsemantic and architectural-spatial layers. Given the current challenges, the regeneration of sacredspaces requires a balanced approach that includes not only functional adaptation or restoration, butalso a careful analysis of historical and spatial layers. A scenario-based, variable, and flexibleapproach is aimed at integrating a new purpose into the sacred space without losing its spiritual andsemantic meanings. The choice of the project concept for the scenario is justified by a number offactors that will set the limits of permissible intervention in the sacred environment. Depending onthe types of sacred spaces, their historical evolution, architectural and functional transformations,state of preservation, architectural and urban planning potential, there is a need to structureapproaches to their regeneration. The study considers the following typology of project scenariosfor the regeneration of sacred spaces: conservation-museum, hybrid sacred-public, adaptivecultural,landscape-memorial.Confirmation of the feasibility of design scenarios for the regeneration of sacred spacespredicts sustainable development, taking into account the visible and invisible layers of thearchitectural environment. The prospects for the development of the scenario method will providethe prerequisites for the creation of scientifically sound design solutions for the restoration of sacredspace.
Keywords: architectural heritage; sacred space, regeneration; design scenarios